2018
DOI: 10.1093/cvr/cvy166
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting vascular and metabolic impact of the IL-33/sST2 axis

Abstract: Interleukin 33 (IL-33), which is expressed by several immune cell types, endothelial and epithelial cells, and fibroblasts, is a cytokine of the IL-1 family that acts both intra- and extracellularly to either enhance or resolve the inflammatory response. Intracellular IL-33 acts in the nucleus as a regulator of transcription. Once released from cells by mechanical stress, inflammatory cytokines, or necrosis, extracellular IL-33 is proteolytically processed to act in an autocrine/paracrine manner as an 'alarmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
107
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 197 publications
0
107
0
1
Order By: Relevance
“…Less consistent is the behavior of IL‐33, an interleukin involved in the maintenance of tissue homeostasis, resolution of inflammation, and repair of tissue damage . IL‐33 is considered to have pro‐ and anti‐inflammatory actions and it is released after cell injury, acting as an alarm signal that alerts immune cells about tissue damage . Our results showed a decreased IL‐33 expression in GDM‐derived AMSCs whereas in vitro control AMSCs exposed to a GDM‐like milieu showed an upward trend.…”
Section: Discussionmentioning
confidence: 56%
“…Less consistent is the behavior of IL‐33, an interleukin involved in the maintenance of tissue homeostasis, resolution of inflammation, and repair of tissue damage . IL‐33 is considered to have pro‐ and anti‐inflammatory actions and it is released after cell injury, acting as an alarm signal that alerts immune cells about tissue damage . Our results showed a decreased IL‐33 expression in GDM‐derived AMSCs whereas in vitro control AMSCs exposed to a GDM‐like milieu showed an upward trend.…”
Section: Discussionmentioning
confidence: 56%
“…47,48 We showed previously the intracellular expression of IL-33 in human cardiac myocytes and fibroblasts, and the release of IL-33 during necrosis of these cells. 27 Moreover, the "decoy" receptor for IL-33, sST2, was shown to have predictive value in patients with coronary artery disease and HF 16,[49][50][51] as well as in critically ill patients. 52 In our study presented here, we found that fluvastatin is able to reduce secretion of sST2 from human cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As an inflammatory mediator IL-33 plays a role in a variety of diseases such as bronchial asthma, inflammatory bowel diseases, and rheumatoid arthritis. 16 On the other hand, IL-33 antagonised prohypertrophic stimuli in rat neonatal cardiomyocytes and exhibited an anti-hypertrophic effect after transverse aortic constriction (TAC) in mice. 21 Furthermore, IL-33 protected rat neonatal cardiomyocytes from hypoxia-induced apoptosis and improved cardiac function in rats after experimental myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations